DESIGN, CONSTRUCTION AND EVALUATION OF RUNOFF WATER HARVESTING POND FOR SMALLHOLDER FARMING - Ahmed, Bayan; Gemeda, Fikadu (International Journal of Research -GRANTHAALAYAH, 2021)
Rainfall shortage and variability constrain crop production of smallholder farmers in Ethiopia is the main problem. For this supplementary irrigation by run off harvesting is strategic pathway to reduce poverty in rural drought prone areas for enhancing agricultural productivity and boosting farm income. For this, this study is conducted to Design, construction and evaluation of runoff water harvesting Pond for supplementary irrigation to addressing inherent crop failures under the rain fed agriculture due to mainly erratic rainfall. For this design climatic and soil data were input to determine seasonal crop water requirement (CWR) of onion and evaporation loss of water from water surface. Then the performances of water harvested verses area irrigate were evaluated. To make this study more economical the water harvester capacity decreed by two fold and water harvesting made at two times. Seasonal volume crop water requirement (CWR) of onion for farm area 2500 m2 and evaporation loss of water from water surface of 121 m2 and total volume of seasonal water need were 382.05,53.38 and 435.43 m3 respectively. The geo-membrane laminated water harvester that has capacity of 223 m3 was designed and constructed. From on field performance shows, this volume of water harvested twice can irrigate 0.25ha by supplementary irrigation using water saving irrigation technology (treadle pump) by over showering and was produced 4.2 tone/ha. The investment, operation and production costs were 63116, 1125 and 6675 ETH birr respectively. The total cost was 70,916 birr and The growth return of 0.25ha was 15,750 birr/year (1050kg*15 birr/kg). This show the farmer can return 22.21% of their investment cost. So it is recommended to the government and non-government to initiate the farmers at lower stream of the catchment to harvest run off water and use for supplementary irrigation to increase their income.